Konseling Behavioral dalam Meningkatkan Konsentrasi Belajar Peserta Didik Sekolah Menegah Pertama Negeri 1 Hulu Sungkai Kabupaten Lampung Utara - Kamil, Badrul; Olvatika, You Pensi (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2015)
The purpose of this research is to know whether group counseling with self-management techniques can improve the confidence of students SMPN 1 Hulu Sungkai Kabupaten Lampung Utara. This research uses experimental method with One-Group Pretest-Posttest design. The sample of research as many as 10 students taken by using technique of Purposive Sampling. Data collection was done by using questionnaire technique in the form of scale of learning concentration and observation. The results showed that the hypothesis Ha accepted while the hypothesis Ho rejected. This is proven by data analysis result using pretest and posttest test obtained 49 and posttest 77,3. The results of this study concluded that group counseling with self-management techniques can improve the learning concentration of students SMPN 1 Hulu Sungkai Kabupaten Lampung Utara.